2011 International Topical Meeting on Microwave Photonics Jointly Held With the 2011 Asia-Pacific Microwave Photonics Conferenc 2011
DOI: 10.1109/mwp.2011.6088657
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of 5-Gb/s polarization-multiplexed fiber-wireless MIMO systems

Abstract: Abstract-We experimentally demonstrate a 5-Gb/s fiber-wireless transmission system combining optical polarization-divisionmultiplexing (PDM) and wireless multiple-input, multiple-output (MIMO) spatial multiplexing technologies. The optical-wireless channel throughput is enhanced by achieving a 4b/s/Hz spectral efficiency. Based on the implementation of constant modulus algorithm (CMA), the 2×2 MIMO wireless channel is characterized and adaptively equalized for signal demodulation. The performance of the CMA-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…where the two items on the right side of the equation are the Jones transmission elements of fiber optics and wireless links. In [56], the ROF network transmission of 5 Gb/s based on PDM and MIMO has been successfully verified. In [57], it is confirmed that 224 Gb/s information data can be transmitted.…”
Section: Optical Pdm Combined With Mimomentioning
confidence: 95%
See 1 more Smart Citation
“…where the two items on the right side of the equation are the Jones transmission elements of fiber optics and wireless links. In [56], the ROF network transmission of 5 Gb/s based on PDM and MIMO has been successfully verified. In [57], it is confirmed that 224 Gb/s information data can be transmitted.…”
Section: Optical Pdm Combined With Mimomentioning
confidence: 95%
“…In addition, it is necessary to introduce the DSP part of the receiver. Compared with the ADC and the basic DSP algorithm in the previous section [56,59,60], the DSP algorithm of this structure is partly complex. Its sequence block diagram is shown in Figure 13.…”
Section: Advanced Multilevel Modulationmentioning
confidence: 99%
“…However, this method limits the number of MIMO streams per wavelength to only two. Among these methods, the most used and proven to be successful are: PDM [6,40,[50][51][52][53][54][55][56][57][58][59][60], using comb techniques to generate multiple wavelengths [49,[61][62][63][64] and also hybrid method between them as shown in Figure 8c [6]. It takes benefit from the optical frequency comb techniques and high bandwidth optical modulators (up to 100 GHz) as shown in Figure 8b [64][65][66][67], and multiple widely separated wavelengths can be produced from one continuous-wave (CW) laser.…”
Section: Wireless Mimo Signals Over Fibre Techniquesmentioning
confidence: 99%
“…The work in [17] tries to attain the fairness guarantee among different traffic flows and to maximize the network throughput. Some works like [18][19][20][21][22][23] address signal processing issues for better performance of the links in Fi-Wi structure.…”
Section: Journal Of Engineeringmentioning
confidence: 99%